2014
DOI: 10.2478/amm-2014-0189
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Parameters of Sand Moulds in Compaction Process by Use of the Industrial Computer Tomography (ICT)

Abstract: One main problem in moulding is the proper characterization of the local density of the mould, the best without its destroying, for assessment the quality of the mould and to compare results of compaction modeling with experimental results. Industrial computer tomography (ICT) is a technique that allows the non-destructive and contact-free visualization and characterization of the internal and external parts of physical objects including also sand moulds. It is possible to apply ICT technique for the specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In this sense, some works were performed earlier by (Degruyter et al, 2010) combining LBM and X-ray µ-CT for the calculation of permeability of volcanic pumices. (Kadauw, 2014) characterized the local density of sand mold using industrial computed tomography, and found good agreement with the experimental density of sand mold. Some typical results were reported recently by (Sivarupan et al, 2018) for the use of X-ray µ-CT to characterize the additively processed porous structure like 3DP sand mold.…”
Section: Introductionmentioning
confidence: 60%
“…In this sense, some works were performed earlier by (Degruyter et al, 2010) combining LBM and X-ray µ-CT for the calculation of permeability of volcanic pumices. (Kadauw, 2014) characterized the local density of sand mold using industrial computed tomography, and found good agreement with the experimental density of sand mold. Some typical results were reported recently by (Sivarupan et al, 2018) for the use of X-ray µ-CT to characterize the additively processed porous structure like 3DP sand mold.…”
Section: Introductionmentioning
confidence: 60%
“…Numerous research works [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] and the documents of the VDI/VDE 2630 association from the year 2009 [17] allow only for the determination of the accuracy associated with the geometry measurement errors, scanning errors, determination of scan resolution or dimensions-material dependence.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the typical manufacturing applications, 3D techniques are also widely used in laboratory structural studies [1][2][3][4][5][6][7][8][9][10], qualitative and quantitative analysis [6][7][8][9][10], or other high-speed measurements of specific materials' properties, made for the sole purpose of manufacturing processes. The versatility of these research methods allows its use in many industries, from timber industry (quality assessment of wood at sawmills) [4], to the highly specialized electrotechnic and electronic companies [2], to medical applications [5].…”
Section: Introductionmentioning
confidence: 99%